Influence of outside temperature on the operation of the adsorption chiller - Grzebielec, Andrzej; Laskowski, Rafał; Ruciński, Adam (International Conference “Environmental Engineering”, 2017)
Adsorption refrigeration systems are characterized by a lower coefficient of performance than the compressor type device or even absorption, but can utilize waste heat at lower temperature. The aim of the study was to determine which external parameter has the greatest impact on the efficiency of the adsorption device. As a result of experimental studies there was found that this is not the temperature of the feed but particularly the temperature of external air. For this reason, it is recommended that the adsorption device should cooperate with evaporative spray coolers, instead of with popular dry coolers. This solution will increase annual efficiency of adsorption unit approx. by 25% and significantly reduce the costs of cold generation.